ENZIMATIC HYDROLYSIS PROCESS FOR INCREASING GLUCOSE LEVELS FROM COCONUT HUSK WASTE - Anggorowati, Dwi Anna; Sriliani, Sriliani; Artiyani, Anis; Setyawati, Harimbi; J, Kevin (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2021)
Coconut husk waste is waste that has not been used optimally, generally only as a craft material. Seeing the composition of coconut husk, it has the potential to be used as an alternative fuel, one of which is to produce bioethanol products. The purpose of this research was to utilize coconut husk waste as raw material for bioethanol production and to assess the effect of the number of enzymes and time of hydrolysis on the glucose levels produced. In this research, the authors focused on obtaining glucose levels from coconut husks by hydrolysis using cellulase enzymes with an activity of 700 EGU/g. The variations used in this research were the volume of cellulase enzymes (2, 3, 4, 5, 6) ml and the hydrolysis time (4, 8, 12) hours. After the coconut husk undergoes physical and chemical treatment using 10% NaOH, there is a decrease in lignin levels from 44% to 14% and there is an increase in cellulose levels from 24% to 38%, and the use of a cellulase enzyme volume of 2 ml with a hydrolysis time of 4 hours was more optimal with a glucose level of 0.32%.